Development of Amine-Functionalized Metal-Organic Frameworks Hollow Fiber Mixed Matrix Membranes for CO2 and CH4 Separation: A Review - Sunder, N. (2022)
CO2 separation from raw natural gas can be achieved through the use of the promising membrane-based technology. Polymeric membranes are a known method for separating CO2 but suffer from trade-offs between its permeability and selectivity. Therefore, through the use of mixed matrix membranes (MMMs) which utilizes inorganic or hybrid fillers such as metal-organic frameworks (MOFs) in polymeric matrix, the permeability and selectivity trade-off can be overcome and possibly surpass the Robeson Upper Bounds. In this study, various types of MOFs are explored in terms of its structure and properties such as thermal and chemical stability. Next, the use of amine and non-amine functionalized MOFs in MMMs development are compared in order to investigate the effects of amine functionalization on the membrane gas separation performance for flat sheet and hollow fiber configurations as reported in the literature. Moreover, the gas transport properties and various challenges faced by hollow fiber mixed matrix membranes (HFMMMs) are discussed. In addition, the utilization of amine functionalization MOF for mitigating the challenges faced is included. Finally, the future directions of amine-functionalized MOF HFMMMs are discussed for the fields of CO2 separation. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.